1997
DOI: 10.1038/sj.bjp.0701396
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory activity of cationic lipids

Abstract: 1 The e ect of liposome phospholipid composition has been assumed to be relatively unimportant because of the presumed inert nature of phospholipids. 2 We have previously shown that cationic liposome formulations used for gene therapy inhibit, through their cationic component, the synthesis by activated macrophages of the pro-in¯ammatory mediators nitric oxide (NO) and tumour necrosis factor-a (TNF-a).3 In this study, we have evaluated the ability of di erent cationic lipids to reduce footpad in¯ammation induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 52 publications
1
34
0
1
Order By: Relevance
“…The reason for the initial drop in disease activity in the control group Gene Therapy of mice given vector plasmid is uncertain. It may be related to an effect on macrophage function of the liposomes themselves since DC-Chol-containing liposomes can reduce inflammation by interfering with macrophage nitric oxide and TNF production 59 or toxicity of that particular preparation of liposome-DNA complexes. However, the effect of transfection with IL-10 expression plasmid was over and above this non-specific effect and the reduction in disease was sustained.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the initial drop in disease activity in the control group Gene Therapy of mice given vector plasmid is uncertain. It may be related to an effect on macrophage function of the liposomes themselves since DC-Chol-containing liposomes can reduce inflammation by interfering with macrophage nitric oxide and TNF production 59 or toxicity of that particular preparation of liposome-DNA complexes. However, the effect of transfection with IL-10 expression plasmid was over and above this non-specific effect and the reduction in disease was sustained.…”
Section: Discussionmentioning
confidence: 99%
“…Amphiphiles, such as lecithin, form spherical structures in which the polar heads protect the nonpolar interior against rapid degradation. The nonviral composition, lack of cytotoxicity, increased infectivity, and anti-inflammatory properties have made the use of cholesterol-containing cationic liposomes an attractive approach for dermal gene therapy and for ameliorating the burn-induced hypermetabolic response (Filion and Philips, 1997;Jeschke et al, 1999). The mechanisms of gene transfer, biodistribution properties, systemic organ transfection or deposition, cellular uptake mechanisms, and whether the translated protein is biologically effective in the skin has not been studied in detail.…”
Section: Discussionmentioning
confidence: 99%
“…This may reflect differences in the physical structure of the three cationic lipids. Filion and Phillips 10 have demonstrated that DOTAP can suppress NO production and TNF-␣ secretion from activated macrophages. It was suggested that DOTAP may suppress activated macrophages by inhibiting protein kinase C. Because DOTAP has a glycerol backbone and is structurally similar to the natural ligand for protein kinase C, diacylglycerol, it may represent a more effective inhibitor of protein kinase C function than DOTMA or DODAC, thereby leading to a more rapid resolution of lipoplex-induced inflammation.…”
Section: Cytokines Released Into the Peritoneal Exudatementioning
confidence: 99%
“…10 Those studies demonstrated that parenteral treatment with a variety of structurally distinct cationic lipids could suppress the inflammation induced by a footpad injection of carageenan or sheep red blood cells in sensitized mice. In addition, i.p.…”
Section: Cytokines Released Into the Peritoneal Exudatementioning
confidence: 99%
See 1 more Smart Citation